Efforts To Prevent Depression For Humans Are Reviewed From The Benefits Of Psychology - Ferdi Sambo; Endang Pasaribu; Guntur Hamonangan Sahat Silaban; Merri Natalia Situmorang (Riviera Publishing, 2025)
Depression is a common and serious mental health disorder that affects individuals across age, gender, and social boundaries. This study investigates efforts to prevent depression from the perspective of psychological benefits, using a survey method with a sample of 25 individuals aged 17–50 who have experienced depression. The research employs a multidisciplinary psychological framework including cognitive-behavioral theory, social psychology, and personality psychology to understand the root causes and design preventive strategies. The findings emphasize the effectiveness of developing adaptive coping skills, fostering social support systems, and enhancing public awareness through mental health education. Additionally, online-based psychological interventions such as internet-based cognitive behavioral therapy (ICBT) are shown to provide flexible and accessible support. A distinctive feature of this research is the integration of Christian faith-based practices—such as prayer, scripture reflection, and faith community engagement—as complementary tools to psychological approaches. These spiritual dimensions strengthen individuals' emotional and moral resilience, contributing to more effective depression prevention. The results also highlight that social factors are the dominant cause of depression (59%), followed by biological, psychological, and economic factors. The study recommends tailored preventive interventions that consider individual personality types, social context, and spiritual needs. Implications of this research support a holistic model for mental health prevention and call for further exploration into the interplay between psychological and spiritual resilience frameworks in mitigating depression.